Brain-Derived Neurotrophic Factor Inhibits Human Immunodeficiency Virus-1/gp120-Mediated Cerebellar Granule Cell Death by Preventing gp120 Internalization - Bachis, Alessia (J Neurosci, 2003)
The human immunodeficiency virus type 1 (HIV-1) envelope protein gp120 has been implicated in the pathogenesis of HIV-1 dementia. Thus, inhibition of gp120 activity could reduce HIV toxicity in the brain. We have used primary cultures of rat cerebellar granule cells to examine mechanisms whereby gp120 causes cell death and to characterize neuroprotective agents. gp120 induced a time- and concentration-dependent apoptotic cell death, which was caspase-3-mediated but caspase-1 independent, and was totally blocked by the irreversible caspase-3-like protease inhibitor N-acetyl-Asp-Glu-Val-Asp-chloromethylketone. Caspase-3 activation was observed only in neurons that internalize gp120, indicating that internalization is key to gp120 toxicity. Because brain-derived neurotrophic factor (BDNF) prevents caspase-3-mediated neuronal cell death, we examined whether BDNF could prevent gp120-mediated apoptosis. Preincubation of neurons with BDNF before the addition of gp120 reduced caspase-3 activation, and consequently rescued 80% of neurons from apoptosis. Most importantly, BDNF reduced the levels of CXC chemokine receptor-4 (CXCR4), a receptor that mediates HIV-1 gp120-induced apoptosis. This effect correlated with the ability of BDNF to reduce gp120 internalization and apoptosis. Moreover, BDNF blocked the neurotoxic effect of stromal-derived factor-1α, a natural ligand for CXCR4, further establishing a correlation between neuroprotection and downregulation of CXCR4. We propose that BDNF may be a valid therapy to slow down the progression of HIV/gp120-mediated neurotoxicity.